Mergers when prices are negotiated: Evidence from the hospital industry - Gautam Gowrisankaran; Aviv Nevo; Robert Town (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2013)
We estimate a bargaining model of competition between hospitals and managed care organizations (MCOs) and use the estimates to evaluate the effects of hospital mergers. We find that MCO bargaining restrains hospital prices significantly. The model demonstrates the potential impact of coinsurance rates, which allow MCOs to partly steer patients towards cheaper hospitals. We show that increasing patient coinsurance tenfold would reduce prices by 16%. We find that a proposed hospital acquisition in Northern Virginia that was challenged by the Federal Trade Commission would have significantly raised hospital prices. Remedies based on separate bargaining do not alleviate the price increases.
Keywords: L11; L13; L31; L38; I11; I18; 330; Hospitals; Mergers; Bargaining; Oligopoly; Health Insurance